Reconstrução de imagens tomográficas tipo DICOM pela técnica de vetorização aplicada a fabricação de próteses via prototipagem rápida - Coutinho, Karilany Dantas (2014)
Currently there is a growing incidence of malignancies and the prospect of cure. In Brazil and in the world there are a great number of maimed because of head and neck cancer and oral cancer. With this new reality, health professionals began to realize that, in addition to tumor removal and disposal of the affected cells also became necessary to search for the rehabilitation, also in an attempt to ensure the quality of life of the individual. Computed tomography and Magnetic Resonance Imaging are two techniques commonly used to capture information of human anatomy. The Rapid Prototype (RP) is a relatively recent to produce objects with complex shapes technique, being obtained directly through three-dimensional digital data. This paper describes a system that integrates methods for three-dimensional reconstruction and rapid prototyping techniques, enabling the creation of medical models (biomodels) through tomographic data. These models can be manufactured using processes that are useful in many medical applications, such as: assist in diagnosis, planning treatment, guiding surgical procedures and prosthesis manufacturing. The 3D models manufactured via printer are constructed by adding layers of material, layer by layer. The research in question was based on a study of a clinical case of a patient Liga Norte-Riograndense Contra o Câncer (LNRCC), located in Natal / RN, the study patient had a malignant lesion in the left palate. This article describes the procedures for the acquisition of medical images in DICOM format, the conversion of these files in STL format engineering and finally to make the prosthesis via 3D prototyping